1979
DOI: 10.1139/p79-077
|View full text |Cite
|
Sign up to set email alerts
|

An improved value for the electron affinity of the negative hydrogen ion

Abstract: An expression is derived for the lifetime of a negative ion in a weak and static electric field. Using this expression, existing experimental data are analyzed to improve the empirical value of the electron affinity of the negative hydrogen ion by an order of magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…Studies on Lorentz stripping of the H 2 ion have been reported in several papers [2][3][4]. The rest-frame lifetime (t) of the H 2 ion in a magnetic field is given by Scherk [3] and Jason et al [4] as follows:…”
Section: Lorentz Stripping Of H 2 Ions and H 0 Atom Excited Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on Lorentz stripping of the H 2 ion have been reported in several papers [2][3][4]. The rest-frame lifetime (t) of the H 2 ion in a magnetic field is given by Scherk [3] and Jason et al [4] as follows:…”
Section: Lorentz Stripping Of H 2 Ions and H 0 Atom Excited Statesmentioning
confidence: 99%
“…The rest-frame lifetime (t) of the H 2 ion in a magnetic field is given by Scherk [3] and Jason et al [4] as follows:…”
Section: Lorentz Stripping Of H 2 Ions and H 0 Atom Excited Statesmentioning
confidence: 99%
“…A negative ion, traversing a distance I in a region where there is a magnetic field B, has a probability to be stripped, and thus lost, given by [2,3] P = 1 -exp(-Z/Z,), '(1) where the stripping length with Al = 2.704 x cally I c< I,, and the stripping probability is small. kG-m, A2 = 149.j kG, and B is expressed in kG and I, in meter.…”
Section: The Spallation Neutron Sourcementioning
confidence: 99%
“…4 Greater accuracy was then achieved by Chupka, Dehmer, and Jivery 5 giving 6083͑ϩ11,Ϫ3͒ cm Ϫ1 . In 1979, Scherk 6 reported a value of 6085.5Ϯ3.3 cm Ϫ1 . Then in 1991, Lykke, Murray, and Lineberger 7 achieved a 20-fold improvement in accuracy obtaining 6082.99Ϯ0.…”
Section: Introductionmentioning
confidence: 99%